High Acoustic Impedance and Attenuation Backing for High-Frequency Focused P(VDF-TrFE)-Based Transducers - Toffessi Siewe, Sean; Callé, Samuel; Vander Meulen, François; Valente, Damien; Grégoire, Jean-Marc; Banquart, Aline; Chevalliot, Stéphanie; Capri, Arnaud; Levassort, Franck (Sensors (Basel, Switzerland), 2023)
Backing materials with tailored acoustic properties are beneficial for miniaturized ultrasonic transducer design. Whereas piezoelectric P(VDF-TrFE) films are common elements in high-frequency (>20 MHz) transducer design, their low coupling coefficient limits their sensitivity. Defining a suitable sensitivity–bandwidth trade-off for miniaturized high-frequency applications requires backings with impedances of >25 MRayl and strongly attenuating to account for miniaturized requirements. The motivation of this work is related to several medical applications such as small animal, skin or eye imaging. Simulations showed that increasing the acoustic impedance of the backing from 4.5 to 25 MRayl increases transducer sensitivity by 5 dB but decreases the bandwidth, which nevertheless remains high enough for the targeted applications. In this paper, porous sintered bronze material with spherically shaped grains, size-adapted for 25–30 MHz frequency, was impregnated with tin or epoxy resin to create multiphasic metallic backings. Microstructural characterizations of these new multiphasic composites showed that impregnation was incomplete and that a third air phase was present. The selected composites, sintered bronze–tin–air and sintered bronze–epoxy–air, at 5–35 MHz characterization, produced attenuation coefficients of 1.2 and >4 dB/mm/MHz and impedances of 32.4 and 26.4 MRayl, respectively. High-impedance composites were adopted as backing (thickness = 2 mm) to fabricate focused single-element P(VDF-TrFE)-based transducers (focal distance = 14 mm). The center frequency was 27 MHz, while the bandwidth at −6 dB was 65% for the sintered-bronze–tin–air-based transducer. We evaluated imaging performance using a pulse-echo system on a tungsten wire (diameter = 25 μm) phantom. Images confirmed the viability of integrating these backings in miniaturized transducers for imaging applications.